The relationship between motivation, supervision, education and training with the ability of health cadres in promoting the health of pregnant women in Sleman Regency, Yogyakarta, Indonesia - Istri Yuliani; Bhisma Murti; Endang Sutisna; Tedjo Danudjo Oepomo (Universitas 'Aisyiyah Yogyakarta, 2019)
The World Health Organization (WHO) estimates that 15% - 20% of pregnant women experience complications. If this problem does not receive adequate treatment, pregnancy complications can contribute to maternal mortality, therefore detecting from the beginning the presence of abnormalities, complications, and complications of pregnancy must be carried out proactively by both health workers and the community, one of them by the health cadres. This study aims to determine the relationship between motivation, supervision, education and training on the ability of the health cadres in the promotion of health of pregnant women. The study was conducted on 7 February to 6 May 2016. This research was an explanatory study with quantitative research methods using a cross-sectional approach. The number of samples was 269 active health cadres. The sampling technique is multi-stage cluster random sampling. Independent variables include motivation, supervision, education and training. The dependent variable is the ability of the health cadres to promote the health of pregnant women. Data collection using a questionnaire, data analysis using Path Analysis. Factors related to the ability of the health cadres in the promotion of health promotion for pregnant women include: motivation (b = 0.68, 95% CI = 0.16 to 1.42, p = 0.01); supervision (b = 1.11, CI 95% = 0.58 to 1.65, p = 0.001), education and training (b = 0.88, 95% CI = 0.36 to 1.21, p = 0.001). Factors related with motivation include: supervision (b = 0.61. 95% CI = 0.13 to 1.11, p = 0.01); education and training: (b = -0.04, 95% CI = -0.52 to 0.44, p = 0.86). df = 1; AIC = 707.81; BIC=732.29. There is a relationship between motivation, supervision, education and training with the ability of health cadres to promote the health of pregnant women. Supervision is the most related factor. Supervision is related to motivation, good supervision will increase the motivation of health cadres, while education and training relate to motivation, health cadres with good education and training, reduce motivation in health promotion, but not statistically significant.